A cross-sectional study of symptoms and health-related quality of life in menopausal-aged women in China - Tamlyn A. Rautenberg; Shu Kay Angus Ng; Martin Downes (BMC, 2023)
Abstract Objective To measure symptoms and health-related quality of life in a cross-sectional cohort of menopausal-aged women in China. Method A cross-sectional survey was conducted in a general population cohort of 2,000 Chinese females over the age of 45 years. Patients completed the Chinese version of the EuroQol-5D five level (EQ5D5L) health-related quality of life instrument via Personal Digital Assistant. Raw scores were converted to utility tariffs using value sets for China. Statistical analysis included Pearson's chi-square test, z test for multiple comparisons with adjustment by the Bonferroni method, independent-sample t-test, ANOVA, and adjustment by the Tukey method for multiple comparison. Results were considered statistically significant when p < 0.05 and the study was reported according to the STROBE recommendations. Results In a cohort of 2000 women, 732 (37%) were premenopausal, 798 (40%) were perimenopausal and 470 (23%) were postmenopausal. Perimenopausal women reported significantly more symptoms (91%) compared to premenopausal (77%) and postmenopausal (81%) women. Health-related quality of life was significantly lower in symptomatic perimenopausal women compared to premenopausal (0.919, p < 0.05) and postmenopausal (0.877, p < 0.05) women. Within each group there was a statistically significant difference between the health-related quality of life of women with symptoms compared to without symptoms. Conclusion The perimenopausal phase of menopause is associated with significantly more symptoms and significantly lower HRQoL compared to premenopausal and postmenopausal phases.